Task-dependent modulation of spinal and transcortical stretch reflexes linked to motor learning rate - Dimitriou, Michael (Behavioral neuroscience, 2018)
It is generally believed that task-dependent control of body configuration ("posture") is achieved by adjusting voluntary motor activity and transcortical "long-latency" reflexes. Spinal monosynaptic circuits are thought not to be engaged in such task-level control. Similarly, being in a state of motor learning has been strongly associated only with an upregulation of feedback responses at transcortical latencies and beyond. In two separate experiments, the current study examined the task-dependent modulation of stretch reflexes by perturbing the hand of human subjects while they were waiting for a "Go" signal to move at the different stages of a classic kinematic learning task (visuomotor rotation). Although the subjects had to resist all haptic perturbations equally across task stages, the study leveraged that task-dependent feedback controllers may already be "loaded" at the movement anticipation stage. In addition to an upregulation of reflex gains during early exposure to the visual distortion, I found a relative inhibition of reflex responses in the "washout" stage (sensory realignment state). For more distal muscles (brachioradialis) this inhibition also extended to the monosynaptic reflex response ("R1"). Moreover, these R1 gains reflected individual motor learning performance in the visuomotor task. The results demonstrate that the system's "control policy" in visuomotor adaptation can also include inhibition of proprioceptive reflexes, and that aspects of this policy can affect monosynaptic spinal circuits. The latter finding suggests a novel form of state-related control, probably realized by independent control of fusimotor neurons, through which segmental circuits can tune to higher-level features of a sensorimotor task. (PsycINFO Database Record